IN VITRO EFFECTS OF POLYSTYRENE NANOPLASTICS ON HUMAN SPERM MOTILITY AND MITOCHONDRIAL ACTIVITY - Oliveira, Beatriz Teixeira de; Carvalho, Camila Santos de; Pinto, Cristiana Livramento Oliveira; Gonçalves, Nicoly Caixêta; Perini, Hugo Felix; Siervo, Gláucia (Acta Biologica Brasiliensia, 2025)
It is estimated that approximately 350 million tons of plastic become waste through physical and chemical processes, generating microplastics and nanoplastics. Considering the increasing global production of plastics and their potential environmental and human health impacts, this study evaluated the effects of polystyrene nanoplastics (PS-NP) on human sperm parameters in vitro. Spermatozoa from healthy volunteers (n=7) were collected and included only if the samples met the World Health Organization’s normality criteria. Cells were isolated using the swim-up technique in BWW medium and exposed to PS-NP at concentrations of 2, 20, and 200 μg/mL, along with a control group, for 30 and 120 minutes. Sperm motility and mitochondrial activity were assessed. The results showed that intermediate and high concentrations significantly reduced motility and mitochondrial functionality in a concentration- and time-dependent manner. These findings suggest that PS-NPs may impair critical functions for male fertility, highlighting the need for further studies to clarify the underlying mechanisms and reproductive health risks.